2022
DOI: 10.3390/jcm11061681
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease Transmission Prevented in an Endoscopy Unit with Universal Protective Measures and No Systematic Preprocedural Testing

Abstract: Background and aims: Even after two years of pandemic, there are still uncertainties on how to proceed when we schedule endoscopic procedures. During the COVID-19 pandemic, some scientific societies recommended universal preprocedural testing for all patients. However, other societies recommended against and considered enough to maintain strict infection control strategies. Our aim was to evaluate this approach in order to see if it was safe for both patients and healthcare workers to proceed with the endoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In contrast to this study, we did not observe a rapid catch up in the number of CRC cases diagnosed. There are several reasons for this: the unequal restart of CRC screening in the different Spanish regions; the reluctance of patients to participate in these screening programs after a positive FIT result; further challenges faced by endoscopy services in increasing capacity back to prepandemic levels, such as staff absences, infection control measures and additional administrative burden such as telephone triaging and preprocedural SARS‐CoV‐2 testing 28 . These situations can conduct an inequities on the resumption of screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to this study, we did not observe a rapid catch up in the number of CRC cases diagnosed. There are several reasons for this: the unequal restart of CRC screening in the different Spanish regions; the reluctance of patients to participate in these screening programs after a positive FIT result; further challenges faced by endoscopy services in increasing capacity back to prepandemic levels, such as staff absences, infection control measures and additional administrative burden such as telephone triaging and preprocedural SARS‐CoV‐2 testing 28 . These situations can conduct an inequities on the resumption of screening.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reasons for this: the unequal restart of CRC screening in the different Spanish regions; the reluctance of patients to participate in these screening programs after a positive FIT result; further challenges faced by endoscopy services in increasing capacity back to prepandemic levels, such as staff absences, infection control measures and additional administrative burden such as telephone triaging and preprocedural SARS-CoV-2 testing. 28 These situations can conduct an inequities on the resumption of screening. Some studies have suggested that the COVID-19 pandemic can have an uneven effect on CRC outcomes depending on whether and how fast screening is resumed after the pandemic onset.…”
Section: Discussionmentioning
confidence: 99%
“…benefits of such testing is unclear, particularly with the use of other hierarchies of control to prevent the spread of SARS-CoV-2, such as the universal use of face masks, visitor restrictions, environmental cleaning, and vaccination. 3 Prior studies examining the impact of universal laboratory admission screening for SARS-CoV-2 infection are limited (1) by short study periods (ie, weeks to a few months) that occurred early in the COVID-19 pandemic, (2) by study in single hospital settings, and (3) by assessment during periods of low COVID-19 community incidence. [4][5][6][7][8][9][10] As COVID-19 activity continues to wax and wane, it is important to evaluate the experience of admission screening programs.…”
mentioning
confidence: 99%